Mesoporous TUD-1 supported indium oxide nanoparticles for epoxidation of styrene using molecular O-2 - Rahman, Sumbul; Farooqui, Saleem A.; Rai, Aditya; Kumar, Rawesh; Santra, Chiranjit; Prabhakaran, Vinod C.; Bhadu, Gopala Ram; Sen, Debasis; Mazumder, S.; Maity, Sudip; Sinha, Anil K.; Chowdhury, Biswajit (RSC Advances, 2015)
Activation of molecular O-2 by metal or metal oxide nanoparticles is an area of recent research interest. In this work, for the first time, we report that indium oxide nanoparticles of <3 nm size dispersed on mesoporous silica (TUD-1) can activate molecular O-2 and produce styrene epoxide with a selectivity of 60% and styrene conversion around 25% under mild conditions. It is found that neither indium oxide nor TUD-1 themselves respond to the styrene epoxidation reaction. The computational studies provide evidence that an oxygen molecule is highly polarized when it is located near the interface of both surfaces. The kinetic study shows that the reaction is of pseudo-first order and that the activation energy for styrene conversion is 12.138 kJ mol(-1). The catalysts are recyclable for up to four regeneration steps, with the styrene conversion and styrene epoxide selectivity almost unchanged.

Highly stable In-SBA-15 catalyst for vapor phase Beckmann rearrangement reaction - Kumar, Rawesh; Shah, Sneha; Bahadur, Jitendra; Melnichenko, Yuri B.; Sen, Debasis; Mazumder, S.; Vinod, Chathakudath P.; Chowdhury, Biswajit (Microporous and Mesoporous Materials, 2016)
The Indium doped SBA-15 material was prepared by sol-gel method and tested for vapor phase Beckman rearrangement reaction. Among three indium loading, In/Si ratio of 2/100 was found as an optimum composition in terms of caprolactam selectivity (100%) and cyclohexanone oxime conversion (100%). The catalysts were characterized by N-2 adsorption, small-angle X-rays/neutron scattering (SAXS/SANS), XRD, FESEM, HRTEM, EDX, UV, FTIR and NH3-TPD techniques. In-situ SANS experiment was performed on the adsorption of CO2 to detect the micropores in the mesopore wall. All catalysts samples have highly ordered hexagonal structure with well dispersed indium in the silica matrix. The fine tuning of weak and strong acid sites were found in indium doped SBA-15 (In/Si = 2/100) catalyst. The same catalyst showed optimum catalytic performance, high space time yield 114.4 mol/h/g(cat) and high stability till 6 h of reaction without deactivation. The micro-kinetic analysis showed that there were no external and internal diffusion limitations in the SBA-15 catalyst. The reaction mechanism of Beckmann rearrangement over In-SBA-15 has been elucidated. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: e-Caprolactam; In-situ SANS; indium; SAXS; SBA-15